Pengaruh Komitmen Perangkat Daerah, Peran Aparat Pengawasan Intern Pemerintah Dan Budaya Organisasi Terhadap Efektifitas Penyelenggaraan Sistem Akuntabilitas Kinerja Instansi Pemerintah - Amellia Betta; Fefri Indra Arza (Wahana Riset Akuntansi, 2020)
This study aims to examine the effect of regional apparatus commitment, the role of APIP and organizational culture on the effectiveness of the implementation of SAKIP. This research uses agency theory. The population of this research is the organization of regional apparatus (OPD) of Solok City and Solok Regency with total sampling sampling method. Respondents in this study were OPD secretaries and a number of auditors in the District and City Government of Solok. Hypothesis testing uses multiple regression analysis techniques. The results showed that the commitment of the regional apparatus influences the effectiveness of SAKIP. While the role of APIP and organizational culture does not affect the effectiveness of SAKIP.Keywords: Effectiveness of SAKIP Implementation;The Role of APIP; Organizational Culture; Regional Apparatus Commitment